Penguatan Profil Pelajar Pancasila (P5) Pada Kurikulum Merdeka di Sekolah Dasar - Fariha Maulida; Heri Dermawan (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2024)
The introduction of the Merdeka Curriculum resulted in a significant shift in focus towards the character of education, creating space for learning projects aimed at strengthening the profile of Pancasila (P5) students. Learning projects inspired by strengthening the Pancasila student profile (P5) are an important strategy in achieving the goals of character education at the elementary school level. This research aims to strengthen the profile of Pancasila students (P5) in the independent curriculum in elementary schools. Research Method This research adopts a qualitative approach as the main methodological framework, enabling an in-depth investigation of the Strengthening Pancasila Student Profile (P5) project in the Merdeka Curriculum. In identifying the project's impact, SDN Surgery 1 Depok was chosen as the research sample to represent various educational contexts and realities at the elementary level. Data collection was carried out using several methods including direct observation, interviews, and document analysis. Research Results The research results show that the Strengthening the Pancasila Student Profile (P5) learning project in the Independent Curriculum makes a positive contribution to the development of student character at the elementary school level